Develop Hybrid Native and Mobile Web Apps. IN ASP.NET MVC 3. - Church, Shane
Shane Church shows you how to build a mobile Web application with ASP.NET MVC 3 and take advantage of native mobile features such as the camera and accelerometer.
Keywords: Windows phone (Computer file); iOS (Electronic resource); Android (Electronic resource); ASP.NET.; jQuery Mobile